RANCANG BANGUN STASIUN BERGERAK UNTUK PEMANTAUAN KUALITAS AIR SUNGAI - Goib Wiranto (Purifikasi, 2006)
A mobile station is required for conducting analysis in locations where a fixed station is not possible to be constructed. In this paper the design and construction of a mobile station for the analysis of river water quality will be described. The focus of this activity has been put on the monitoring of four river water quality parameters, namely pH, temperature, conductivity, and dissolved oxygen. The method of measurement has been based on continuous flow principle, in which sensors are put inside a flowcell that is continuously filled with river water. The resulting measurement from each parameter is then stored in a data logger unit that can be programmed to automatically send the stored values to a master station. With this technique, a mobile station for the online analysis of river water quality can be realized.